Upgrading and Optimization of Pyrolysis Oil from Corncob (Euphorbia mammillaris) and Peanut (Arachis hypogaea) Shells by Liquid-Liquid Extraction Process - OLALEYE, Gabriel Olayinka; ODETOYE, Temitope Elizabeth; ZUBAIRU, Abdulkadir Ahmed; OLUFOWORA, Fatimah Olamide (ABUAD Journal of Engineering and Applied Sciences, 2024)
The bio-oils from peanut shells and corncobs have limited applications due to high oxygen content, viscosity, acidity, and organic compounds, necessitating upgrading. This study employed liquid-liquid extraction to improve oil quality due to its affordability. Bio-oils were produced via intermediate pyrolysis in a fixed-bed reactor at 450 °C, followed by physicochemical and GC-MS analysis. The need for further treatment led to the use of a low-cost, simple liquid-liquid extraction method. A Box-Behnken experimental design was applied, considering temperature, time, and solvent as parameters. Extraction temperatures of 25 °C, 40 °C, and 55 °C were tested alongside extraction times of 30, 60, and 90 minutes using n-hexane and ethanol as solvents in a 1:2 ratio with bio-oil. N-hexane achieved higher phenolic compound extraction efficiency, yielding 68.21% for corncob bio-oil and 66.94% for peanut shell bio-oil, compared to 60.95% and 58.87% using ethanol at 55 °C. The process also improved pH values from 4.7 to 5.7 for peanut oil and from 4.5 to 5.8 for corncob oil, reducing acidity and operational costs. It was concluded that higher extraction temperatures increased bio-oil yield up to a critical limit, while n-hexane proved more effective than ethanol in enhancing oil quality and reducing acidity, thereby solving transportation and storage challenges.